Reprogramming human A375 amelanotic melanoma cells by catalase overexpression: Reversion or promotion of malignancy by inducing melanogenesis or metastasis - Bracalente, María Candelaria (2016)
Advanced melanoma is the most aggressive form of skin cancer. It is highlymetastatic and dysfunctional in melanogenesis; two processes that are induced byH2O2. This work presents a melanoma cell model with low levels of H2O2 inducedby catalase overexpression to study differentiation/dedifferentiation processes.Three clones (A7, C10 and G10) of human A375 amelanotic melanoma cells withquite distinct phenotypes were obtained. These clones faced H2O2 scavenging by two main strategies. One developed by clone G10 where ROS increased. This resulted in G10 migration and metastasis associated with the increased of cofilin-1 and CAP1. The other strategy was observed in clone A7 and C10, where ROS levels were maintained reversing malignant features. Particularly, C10 was not tumorigenic, while A7 reversed the amelanotic phenotype by increasing melanin content and melanocytic differentiation markers. These clones allowed the study of potential differentiation and migration markers and its association with ROS levels in vitro and in vivo, providing a new melanoma model with different degree of malignancy.